The Heart of Hell : The Soldiers' Struggle for Spotsylvania's Bloody Angle - Wert, Jeffry D. (Book collections on Project MUSE., 2022)
"The struggle over the fortified Confederate position known as Spotsylvania's Mule Shoe was without parallel during the Civil War. A Union assault that began at 4:30 A.M. on May 12, 1864, sparked brutal combat that lasted nearly twenty-four hours. By the predawn hours of May 13, some 17,500 officers and men from both sides had been killed, wounded, or captured when the fighting ceased. The site of the most intense clashes became forever known as the Bloody Angle. Here, renowned military historian Jeffry D. Wert draws on the personal narratives of Union and Confederate troops who survived the fight to offer a gripping story of Civil War combat at its most difficult"--